ANALISIS GAYA BELAJAR DITINJAU DARI HASIL BELAJAR SISWA KELAS V PADA TEMA 8 SUBTEMA 1 PEMBELAJARAN 6 - Wahyu Adiningsih; Widya Kusumaningsih; Kartinah (STKIP Subang, 2023)
The purpose of this research is to investigate the various learning styles of fifth-grade students at SD N Sawah Besar 01 Semarang, as assessed by their learning outcomes in Theme 8, Subtheme 1, Lesson 6. Learning style refers to the way students absorb, organize, and process information acquired during the learning process. Learning outcomes represent the experiences gained by students, including their cognitive abilities in solving given problems. This study employed a qualitative descriptive method. Data collection techniques included observation, questionnaires, and documentation. The research findings indicate differences in learning styles among fifth-grade students, including visual, auditory, and kinesthetic learning styles.